2000
DOI: 10.1002/(sici)1097-4679(200003)56:3<395::aid-jclp15>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

The Rorschach test in clinical diagnosis: A critical review, with a backward look at Garfield (1947)

Abstract: The present article comments on a classic study by Garfield (1947) then reviews research on the Rorschach and psychiatric diagnoses. Despite a few positive findings, the Rorschach has demonstrated little validity as a diagnostic tool. Deviant verbalizations and bad form on the Rorschach, and indices based on these variables, are related to Schizophrenia and perhaps to Bipolar Disorder and Schizotypal Personality Disorder. Patients with Borderline Personality Disorder also seem to give an above-average number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 170 publications
3
83
0
Order By: Relevance
“…The authors of the present article and a colleague recently reviewed the research on the Rorschach and psychiatric diagnoses (Wood, Lilienfeld et al, 2000a, 2000b. We reached the following conclusions:…”
Section: Rorschach Validity: Relationships With Diagnoses and Self-rementioning
confidence: 52%
See 2 more Smart Citations
“…The authors of the present article and a colleague recently reviewed the research on the Rorschach and psychiatric diagnoses (Wood, Lilienfeld et al, 2000a, 2000b. We reached the following conclusions:…”
Section: Rorschach Validity: Relationships With Diagnoses and Self-rementioning
confidence: 52%
“…According to Exner (1991, p. 146), an elevated score on the DEPI "correlates very highly with a diagnosis that emphasizes serious affective problems." However, independent investigators have usually found that diagnoses of depression are not significantly related to scores on the original or revised version of the DEPI, either in adults or adolescents (for reviews, see Jorgensen, Anderson, & Dam, in press;Viglione, 1999;Wood, Lilienfeld, et al, 2000a).…”
Section: Rorschach Validity: Relationships With Diagnoses and Self-rementioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates that the Rorschach can be helpful for detecting conditions characterized by thought disorder (e.g., schizophrenia; see Wood et al, 2000). It is also supported for evaluating dependent personality traits.…”
Section: Research On the Assessment Of Psychopathologymentioning
confidence: 99%
“…A total score more than 198 on the Symptom Check List -90 was a negative predictor for outcome 34 .The Rorschach inkblot is used as a diagnostic tool for psychiatric diagnoses and for particular psychological symptoms 77 . Several Rorschach variables were associated with better outcome.…”
Section: Psychological Predictorsmentioning
confidence: 99%